Obesity and asthma: A focused review. (November 2022) - Tooba, Rubabin; Wu, Tianshi David
Highlights: Obesity appears to worsen asthma severity and control. Lung mechanics, inflammation, and metabolic disease are some mediating factors. Interventions targeting weight loss appear to improve obesity-associated asthma.